High rate multiple drug resistances in HIV-infected patients failing nonnucleoside reverse transcriptase inhibitor regimens in Thailand, where subtype A/E is predominant - Ploenchan Chetchotisakd (2018)
The prevalence of drug resistance was determined among 64 HIV-infected Thai patients who were failed while receiving nonnucleoside reverse transcriptase inhibitor (NNRTI)-based regimens. Eighty-nine percent of patients had 1 or more NNRTI mutation resistances. Almost all patients had resistance to at least 1 nucleoside reverse transcriptase inhibitor (NRTI), and 42% had multiple-NRTI resistance. © 2006 Sage Publications.